Features of the microelement composition of saliva in elderly patients - A. M. Imanov; Y. A. Mazur; E. M. Kakabadze (Эндодонтия Today)
Trace elements contained in human saliva, despite their small amount, perform a number of biological functions and are a reflection of the processes occurring in the body. The ease of sampling, the non-invasiveness of the method determine the high interest on the part of researchers from various fields of medicine in studying the diagnostic capabilities of salivary fluid as an auxiliary method in assessing the functional state of the body, the presence of pathological processes in it, determining the prerequisites for the development of certain diseases and developing preventive measures to prevent them. This is especially true in the diagnosis of elderly patients, due to the increased risk of occurrence and development of many diseases, on the one hand, and the possibility of multiple sampling for analysis, on the other.  The paper analyzes studies on the possibilities of using the method of microelement analysis of saliva in elderly patients in relation to such pathological conditions as the development of cardiovascular and neurodegenerative diseases, a decrease in humoral and local immunity, including the development of chronic immune inflammation as one of the geriatric syndromes of initial asthenia, and also the development of periodontitis and type 2 diabetes. The prerequisites for the use of saliva analysis as the determination of pain biomarkers and Alzheimer's disease biomarkers for the diagnosis of pain syndrome and the diagnosis of Alzheimer's disease, respectively, are noted, which seems to be especially relevant in elderly patients with dementia, suffering from cognitive impairment and unable to communicate. A number of studies have analyzed the age-related changes in the microelement composition of saliva, including changes in the microelement composition of the saliva of women with postmenopausal osteoporosis.  According to the results of the review study, it should be noted that it is promising to study the possibilities of the microelement composition of saliva in elderly patients both as an auxiliary method for diagnosing various pathological conditions and in developing algorithms for the prevention and treatment of a number of diseases, as well as a method for evaluating the effectiveness of ongoing therapeutic procedures.